2018
DOI: 10.1371/journal.pone.0187519
|View full text |Cite|
|
Sign up to set email alerts
|

Evidence for plant-derived xenomiRs based on a large-scale analysis of public small RNA sequencing data from human samples

Abstract: In recent years, an increasing number of studies have reported the presence of plant miRNAs in human samples, which resulted in a hypothesis asserting the existence of plant-derived exogenous microRNA (xenomiR). However, this hypothesis is not widely accepted in the scientific community due to possible sample contamination and the small sample size with lack of rigorous statistical analysis. This study provides a systematic statistical test that can validate (or invalidate) the plant-derived xenomiR hypothesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 82 publications
2
34
0
Order By: Relevance
“…For sequence comparison, we collected 166 xenomiR sequences (positive samples) and 942 non-xenomiR sequences (negative samples). All 166 xenomiRs (Additional file 2: Table S1) were collected from our previous study [26], which were obtained from 388 healthy human samples analyzed by a rigorous bioinformatics pipeline. These miRNAs covered almost all the reported plant-derived xenomiRs so far.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For sequence comparison, we collected 166 xenomiR sequences (positive samples) and 942 non-xenomiR sequences (negative samples). All 166 xenomiRs (Additional file 2: Table S1) were collected from our previous study [26], which were obtained from 388 healthy human samples analyzed by a rigorous bioinformatics pipeline. These miRNAs covered almost all the reported plant-derived xenomiRs so far.…”
Section: Resultsmentioning
confidence: 99%
“…Of interest, the functions of these xenomiRs seem to be consistent with previous studies (see details below). We have shown in our previous paper [26] that the plant miRNAs detected in human bodies are tissue-specific and cannot be fully explained by contamination and provided evidence for the xenomiRs hypothesis. The selective absorption of plant miRNAs by animal bodies could provide an explanation for studies where xenomiRs were not detected in animal bodies.…”
Section: Discussionmentioning
confidence: 97%
“…The absorption of exomiRs in plant food has been a topic of controversy in past years [197,198]. The dietary delivery of miRNAs in humans is at least feasible [199], and several researchers recently found plant exogenous miRs in human samples [16,200]. Indeed, orally delivered therapeutic RNA strands, called short interfering RNA (siRNA) has been demonstrated in vivo [201].…”
Section: Glycans Are Reactive Chemical Speciesmentioning
confidence: 99%
“…pl-miR can enter the human body through the gastrointestinal tract and spread with blood in combination with proteins or as part of exosomes (Buck et al, 2014; Escrevente et al, 2011; Montecalvo et al, 2012; van der Grein & Nolte-’t Hoen, 2014). Many studies have shown that miRNAs that enter the gastrointestinal tract with food (dietary miRNA) are then found in various tissues (Chiang et al, 2015; Jonathan et al, 2013; Liang et al, 2015; Stephen & Snow, 2017; Vaucheret & Chupeau, 2012; Zempleni et al, 2017; Zhang et al, 2019; Zhang et al, 2012; Zhao et al, 2018). For example, аfter consumption of a fresh maize diet most zma-miRNAs were detected in the heart, brain, mammary gland, lung, liver, kidney and serum exosomes of pig (Luo et al, 2017).…”
Section: Introductionmentioning
confidence: 99%